Milk and honey - Kaur, Rupi (Oxford Univ, 2015)
The book is divided into four chapters, and each chapter serves a different purpose. Deals with a different pain. Heals a different heartache. Milk and Honey takes readers through a journey of the most bitter moments in life and finds sweetness in them because there is sweetness everywhere if you are just willing to look.
Keywords: Tham khảo